Literature review on field study of ventilation and indoor air quality performance verification in high-performance commercial buildings in North America. (3rd October 2017) - Emmerich, Steven J.; Teichman, Kevin Y.; Persily, Andrew K.
Abstract : In this article, the authors summarize the results of field studies to evaluate the ventilation and indoor air quality performance in high-performance commercial (nonindustrial and nonresidential) buildings in North America. The authors show that the number of such studies is small and that the ventilation and indoor air quality measurements performed vary widely. For example, only one of the studies directly measured ventilation rates and one additional study used measured carbon dioxide concentrations to estimate these rates. Similarly, the suite of indoor pollutants measured, which generally included some measure of particulate matter and total volatile organic compounds, rarely included measurements of biological contaminants, semi-volatile organic compounds, or ozone. Previously published concepts are discussed for documenting indoor air quality in high-performing buildings during design, construction and commissioning, and after occupancy, and conclude more complete and uniform studies are needed on the economic, environmental, and health implications of ventilation and indoor air quality in high-performance commercial buildings.